EFEKTIVITAS MEDIA VIDEO TERHADAP PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DI SMP NEGERI 3 PEKANBARU - Najatin, Lauzah; Hayati, Susani (Universitas Batam, 2024)
Reproductive health problems are prone to occur in adolescents due to physical growth and self-maturity. Conditions make teenagers a prone period in reproductive health, such as deviant courtship patterns, promiscuous sex behavior, pregnancy that is not cold. These problems will have an impact on reproductive health in adolescents. The purpose of the study was to determine the effectiveness of video media on adolescents' knowledge about reproductive health in SMP Negeri 3 Pekanbaru. This research method is quantitative. This research uses Quasi Experiment Design method with Non Equivalent Control Group approach. The number of samples of the intervention group was 80 people and the control group was 80 people. The sampling technique is simple random sampling. The research was conducted in July 2024, using a reproductive health questionnaire instrument in adolescents. The analysis used was univariate and bivariate analysis using independent T-test. The results showed a pretest Pvalue of 0.289 and a post test Pvalue of 0.000, so it can be seen that there is a difference in students' knowledge about reproductive health between the group given the intervention and the control group that was not given the intervention, which means that there is an effectiveness of video media on adolescents' knowledge about reproductive health. The recommendation of this study is that schools can provide information and can implement it with socialization events through student activities so as to help increase knowledge about adolescent reproductive health.